Study of the structural, electrokinetic and magnetic characteristics of the Er1-xZrxNiSb semiconductor - Romaka, V.A.; Stadnyk, Yu.; Romaka, L.; Krayovskyy, V.; Нoryn A.; Klyzub, P.; Pashkevych, V. (Physics and Chemistry of Solid State, 2020)
Peculiarities of the structural, electrokinetic, energetic, and magnetic characteristics of Er1-xZrxNiSb semiconductive solid solution, х=0–0.10, were studied. It was suggested that when Zr (4d25s2) atoms were introduced into the structure of the ErNiSb half-Heusler phase by substitution of Er (5d06s2) atoms in 4a position, Zr atoms can also simultaneously occupy the 4c position of Ni (3d84s2) atoms. As a result, in Er1-xZrxNiSb semiconductor, the structural defects of donor nature in position 4a and ones of acceptor nature in position 4c were generated simultaneously. In this case, in the band gap of Er1-xZrxNiSb, the energy states of impurity donor and acceptor bands (donor-acceptor pairs) appear and determine the electrical conductivity mechanism of the semiconductor.